Features of the Course of Viral Pneumonia in Young Children - Kholtaeva Fatima Fayzievna (Scholars Digest Publishing, 2023)
This article is devoted to the presentation of information available in the literature about the etiology, pathogenesis, classification, clinical picture of pneumonia in young children.
Keywords: children, pneumonia, diagnostics.